The multipotency‐to‐commitment transition in Caenorhabditis elegans—implications for reprogramming from cells to organs. Issue 6 (1st February 2018) - Spickard, Erik A.; Joshi, Pradeep M.; Rothman, Joel H.
Abstract : In animal embryos, cells transition from a multipotential state, with the capacity to adopt multiple fates, into an irreversible, committed state of differentiation. This multipotency‐to‐commitment transition (MCT) is evident from experiments in which cell fate is reprogrammed by transcription factors for cell type‐specific differentiation, as has been observed extensively in Caenorhabditis elegans . Although factors that direct differentiation into each of the three germ layer types cannot generally reprogram cells after the MCT in this animal, transcription factors for endoderm development are able to do so in multiple differentiated cell types. In one case, these factors can redirect the development of an entire organ in the process of "transorganogenesis". Natural transdifferentiation also occurs in a small number of differentiated cells during normal C. elegans development. We review these reprogramming and transdifferentiation events, highlighting the cellular and developmental contexts in which they occur, and discuss common themes underlying direct cell lineage reprogramming. Although certain aspects may be unique to the model system, growing evidence suggests that some mechanisms are evolutionarily conserved and may shed light on cellular plasticity and disease in humans. Abstract :